Nothing but good intentions: the search for equity and stock price crash risk - Doron Reichmann; Rouven Möller; Tobias Hertel (Journal of Business Economics, 2022)
In this study, we examine whether and how managers' intentions to raise equity are associated with future stock price crash risk. Therefore, we apply modern information retrieval techniques to corporate textual disclosures by constructing document embeddings that preserve contextual relationships in managers' discussions on liquidity and capital resources. Using these document embeddings, we construct a continuous measure of managers' intentions to raise equity. We document that the search for equity is associated with higher future stock price crash risk. Further analyses suggest that managers with stronger intentions to raise equity are more likely to block negative news flow and that these intentions reinforce the effects of earnings manipulation and textual obfuscation on stock price crash risk. In summary, our results suggest that managers' search for equity incentivises managerial bad news hoarding.
Keywords: G12; G14; G32; M41; 650; Stock price crash risk; Information opacity; Agency theory; Natural language processing; Textual disclosures; Equity finance; Information retrieval